Building Students' Learning Experience in Online Learning During Pandemic - Syaharuddin Syaharuddin; Mutiani Mutiani; Muhammad Rezky Noor Handy; Ersis Warmansyah Abbas; Jumriani Jumriani (STAI Hubbulwathan Duri, 2021)
The practice of online learning during a pandemic is ideally able to provide independent learning for students. However, what happens is the loss of a meaningful learning experience. The research aims to describe the implementation of online learning in Banjarmasin and examine the selection of appropriate learning strategies in providing learning experiences for students. The data were sourced from structured interviews of as many as 15 students and five social studies teachers from 3 junior high schools. Structured interview data from the google form were tabulated, described, and analyzed by the social studies teacher in-depth interview through the restatement, description, and interpretation stages. The study results describe that choosing the right learning strategy has helped provide a learning experience for students during the pandemic. The learning strategy that can do is visiting teachers. Teacher visits are carried out with a clear schedule of regular attendance. In addition, teachers can take advantage of several platforms such as; zoom, google classroom, the personal messenger as learning media.